Potensi Teknologi Medan Pulsa Listrik untuk Memperbaiki Kualitas Daging: Sebuah Ulasan - Khothibul Umam Al Awwaly (Faculty of Animal Science Universitas Brawijaya, 2016)
New and emerging robust technologies can play an important role in ensuring a more resilient meat value chain and satisfying consumer demands and needs. One of the new technologies was pulsed electric fields technology. However, the successful application of this technology was in the liquid food substances like fruit juice and milk. Recently, an attempt have been tried to use the pulsed electric fields for semi solid and solid material like meat and meat products. Application of pulsed electric fields in the meat sector could improve the quality of meat, for example the meat tenderness, water holding capacity and microbial count of meat. This paper outlines principles and application range of this technology which have shown potential benefit for improving meat quality.